Triboelectric nanogenerator (TENG) mass spectrometry of falsified antimalarials. (13th August 2018) - Bernier, Matthew C.; Li, Anyin; Winalski, Laura; Zi, Yunlong; Li, Yafeng; Caillet, Céline; Newton, Paul; Wang, Zhong Lin; Fernández, Facundo M.
Abstract : Rationale: An epidemic of low‐quality medicines continues to endanger patients worldwide. Detection of such 'medicines' requires low cost, ambient ionization sources coupled to fieldable mass spectrometers for optimum sensitivity and specificity. With the use of triboelectric nanogenerators (TENGs), the charge required to produce gas‐phase ions for mass analysis can be obtained without the need for high‐voltage electrical circuitry, simplifying and lowering the cost of next‐generation mass spectrometry instruments. Methods: A sliding freestanding (SF) TENG was coupled to a toothpick electrospray setup for the purposes of testing if falsified medicines could be fingerprinted by this approach. Extracts from both genuine and falsified medicines were deposited on the toothpick and the SF TENG actuated to generate electrical charges, resulting in gas‐phase ions for both active pharmaceutical ingredients and excipients. Results: Our previous work had shown that direct analysis in real time (DART) ambient mass spectrometry can identify the components of multiple classes of falsified antimalarial medicines. Experiments performed in this study show that a simple extraction into methanol along with the use of a SF TENG‐powered toothpick electrospray can provide similar detection capabilities, but with much simpler and rugged instrumentation, and without the need for compressed gases or high‐voltage ion source power supplies. Conclusions: TENG toothpick MS allows for rapid analyte ion detection in a safe and low‐cost manner, providing robust sampling and ionization capabilities.